2021
DOI: 10.1002/etc.5174
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcriptomics and Metabolomics to Understand Species Differences in Sensitivity to Chlorpyrifos in Japanese Quail and Double‐Crested Cormorant Embryos

Abstract: Modern 21st‐century toxicity testing makes use of omics technologies to address critical questions in toxicology and chemical management. Of interest are questions relating to chemical mechanisms of toxicity, differences in species sensitivity, and translation of molecular effects to observable apical endpoints. Our study addressed these questions by comparing apical outcomes and multiple omics responses in early–life stage exposure studies with Japanese quail (Coturnix japonica) and double‐crested cormorant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…Overall, few effects of chemical exposure on the metabolome were observed at the doses that we tested. This was notable, given that significant changes were reported at the transcriptional and organismal level in response to several of the chemicals [ 11 , 13 ]. Here, we discuss these results and factors that may have contributed to this outcome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, few effects of chemical exposure on the metabolome were observed at the doses that we tested. This was notable, given that significant changes were reported at the transcriptional and organismal level in response to several of the chemicals [ 11 , 13 ]. Here, we discuss these results and factors that may have contributed to this outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 16 lipids showed a log2FC > |1.5| ( Table 1 ). We previously explored this result in a related study comparing transcriptomic and metabolomic responses to CPF in two avian species: Japanese quail and double-crested cormorant ( Phalacrocorax auritus ) [ 11 ]. We found that CPF had a high impact in Japanese quail ELS liver, disrupting hepatic metabolism, causing oxidative stress, and endocrine disruption (steroid and non-steroid hormones).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations